Dynamics of the Emergence of Bullying Behavior in Elementary Schools in Manggarai Regency - Bebok, Christin Florentin Meinarty; Eka, Angelina Roida; Danal, Paskaliana; Manggul, Makrina Sedista (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2024)
Previous research has indicated that bullying typically emerges during late childhood, often within elementary school settings. Although bullying behaviors are commonly observed among elementary school children, many students remain unfamiliar with the term "bullying". This study aimed to explore both students’ and teachers’ understanding of bullying, as well as the dynamics contributing to the development of such behavior. Employing a case study approach, data were collected through interviews with individuals identified as bullying perpetrators and those closest to them, including peers, teachers, and parents. The findings revealed that both teachers and students recognized bullying as harmful behavior that leads to emotional distress and physical harm. In this case, bullying behavior was associated with aggressive tendencies modeled by parents, and the school failed to provide an adequate response or intervention. These results underscore the importance of establishing a consistent and shared understanding of bullying among all school staff, and fostering collaboration between schools and the broader support systems of children to effectively prevent bullying behavior.